الإحسان ومجالاته وآثاره من المنظور القرآني : دراسة موضوعية - مروان أفندي نصرون (al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2007)
This study aims at uncovering the meaning of “Ihsan” through its linguistic and terminological meanings which are inherent in all the spheres of human life. The study explains the scopes of “Ihsan” and its impact on individuals and society from the Quranic point of view by studying and tracing verses related to “Ihsan”. The study also analyzes other resources such as the books of Quranic exegesis, hadith compilations and other written resources which are relevant to the topic. Among the points that the study manages to put forward are: “Ihsan” is an umbrella term that covers all kinds of relations an individual has, be that with his God or himself or with others; “Ihsan” has the linguistic meaning of the relation of an individual with himself and others by delivering the blessings to one self or to others for their betterment; the terminological meaning of “Ihsan” means the relation between man and his God by constantly observing the presence of the Divine thus sincerely abiding by His commands and refraining from His prohibitions. Therefore, “Ihsan” is said to be in three scopes: “Ihsan” with God, “Ihsan” with the self or soul and finally “Ihsan” with others.